English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2 answers

(x^4+1)
=(x^2+i)(x^2-i)

Sarkartap done a good job
but answer wrong!
Correction:
x^4+1
=(x^2)^2+(1)^2+2x^2-2x^2
=(x^2+1)^2-(x sqrt2)^2
=(x^2+1+xsqrt2)(x^2+1-xsqrt2)

2007-02-04 15:54:40 · answer #1 · answered by seah 7 · 1 0

x^4+1
=(x^2)^2+(1)^2+2x^2-2x^2
=(x+1)^2-(x sqrt2)^2
=(x+1+xsqrt2)(x+1-xsqrt2)

2007-02-05 05:55:09 · answer #2 · answered by alpha 7 · 0 0

fedest.com, questions and answers